Effect of Addition of Two Levels of Urea on Nutritional Value of Molasses Treated Tomato Straw Silage (Journal of Veterinary Medicine and Animal Production, 2022)
The aim of this study was to determine the nutritive value of tomato straw ensiled for one month with two levels of urea and level of molasses, 0.0% urea +5%molasses (control), 3% urea +5%molasses, and 6% urea +5%molasses. Chemical composition of all treatments was determined by laboratory analysis; an in vitro two stages digestibility was carried out and physical character of the silage have been measured. The data was subjected to analysis of variance using complete randomized design (CRD). The study showed that the final pH was decreased and temperature were increased not significantly (p>0.05) while crude protein was increased significantly (p